# Ordinary Differential Equations/Frobenius Solution to the Hypergeometric Equation

In the following we solve the second-order differential equation called the hypergeometric differential equation using Frobenius method, named after Ferdinand Georg Frobenius. This is a method that uses the series solution for a differential equation, where we assume the solution takes the form of a series. This is usually the method we use for complicated ordinary differential equations.

The solution of the hypergeometric differential equation is very important. For instance, Legendre's differential equation can be shown to be a special case of the hypergeometric differential equation. Hence, by solving the hypergeometric differential equation, one may directly compare its solutions to get the solutions of Legendre's differential equation, after making the necessary substitutions. For more details, please check the hypergeometric differential equation

We shall prove that this equation has three singularities, namely at *x* = 0, *x* = 1 and around infinity. However, as these will turn out to be regular singular points, we will be able to assume a solution on the form of a series. Since this is a second-order differential equation, we must have two linearly independent solutions.

The problem however will be that our assumed solutions may or not be independent, or worse, may not even be defined (depending on the value of the parameters of the equation). This is why we shall study the different cases for the parameters and modify our assumed solution accordingly.

## Contents

- 1 The equation
- 2 Solution around
*x*= 0 - 3 Analysis of the solution in terms of the difference γ − 1 of the two roots
- 4 Solution around
*x*= 1 - 5 Analysis of the solution in terms of the difference γ − α − β of the two roots
- 6 Solution around infinity
- 7 Analysis of the solution in terms of the difference α - β of the two roots
- 8 Reference

## The equation[edit]

Solve the hypergeometric equation around all singularities:

## Solution around *x* = 0[edit]

Let

Then

Hence, *x* = 0 and *x* = 1 are singular points. Let's start with *x* = 0. To see if it is regular, we study the following limits:

Hence, both limits exist and *x* = 0 is a regular singular point. Therefore, we assume the solution takes the form

with *a*_{0} ≠ 0. Hence,

Substituting these into the hypergeometric equation, we get

That is,

In order to simplify this equation, we need all powers to be the same, equal to *r* + *c* - 1, the smallest power. Hence, we switch the indices as follows:

Thus, isolating the first term of the sums starting from 0 we get

Now, from the linear independence of all powers of *x*, that is, of the functions 1, *x*, *x*^{2}, etc., the coefficients of *x*^{k} vanish for all *k*. Hence, from the first term, we have

which is the indicial equation. Since *a*_{0} ≠ 0, we have

Hence,

Also, from the rest of the terms, we have

Hence,

But

Hence, we get the recurrence relation

Let's now simplify this relation by giving *a*_{r} in terms of *a*_{0} instead of *a*_{r − 1}. From the recurrence relation (note: below, expressions of the form (*u*)_{r} refer to the Pochhammer symbol).

As we can see,

Hence, our assumed solution takes the form

We are now ready to study the solutions corresponding to the different cases for *c*_{1} − *c*_{2} = γ − 1 (it should be noted that this reduces to study the nature of the parameter γ: whether it is an an integer or not).

## Analysis of the solution in terms of the difference γ − 1 of the two roots[edit]

### γ not an integer[edit]

Then *y*_{1} = *y*|_{c = 0} and *y*_{2} = *y*|_{c = 1 − γ}. Since

we have

Hence, Let *A*′ a_{0} = *a* and *B*′ *a*_{0} = *B*. Then

### γ = 1[edit]

Then *y*_{1} = *y*|_{c = 0}. Since γ = 1, we have

Hence,

To calculate this derivative, let

Then

But

Hence,

Differentiating both sides of the equation with respect to *c*, we get:

Hence,

Now,

Hence,

For *c* = 0, we get

Hence, *y* = *C*′ *y*_{1} + *D*′ *y*_{2}. Let *C*′ *a*_{0} = *C* and *D*′ *a*_{0} = *D*. Then

### γ an integer and γ ≠ 1[edit]

#### γ ≤ 0[edit]

From the recurrence relation

we see that when *c* = 0 (the smaller root), *a*_{1 − γ} → ∞. Hence, we must make the substitution *a*_{0} = *b*_{0} (*c* - *c*_{i}), where *c*_{i} is the root for which our solution is infinite. Hence, we take *a*_{0} = *b*_{0} *c* and our assumed solution takes the new form

Then *y*_{1} = *y*_{b}|_{c = 0}. As we can see, all terms before

vanish because of the *c* in the numerator. Starting from this term however, the *c* in the numerator vanishes. To see this, note that

Hence, our solution takes the form

Now,

To calculate this derivative, let

Then following the method in the previous case, we get

Now,

Hence,

Hence,

At *c* = 1- γ, we get *y*_{2}. Hence, *y* = *E*′ *y*_{1} + *F*′ *y*_{2}. Let *E*′ *b*_{0} = *E* and *F*′ *b*_{0} = *F*. Then

#### γ > 1[edit]

From the recurrence relation

we see that when *c* = 1 - γ (the smaller root), *a*_{γ − 1} → ∞. Hence, we must make the substitution *a*_{0} = *b*_{0}(*c* − *c*_{i}), where *c*_{i} is the root for which our solution is infinite. Hence, we take *a*_{0} = *b*_{0}(*c* + γ - 1) and our assumed solution takes the new form:

Then *y*_{1} = *y*_{b}|_{c = 1 - γ}. All terms before

vanish because of the *c* + γ - 1 in the numerator. Starting from this term, however, the *c* + γ - 1 in the numerator vanishes. To see this, note that

Hence, our solution takes the form

Now,

To calculate this derivative, let

Then following the method in the second case above,

Now,

Hence,

At *c* = 0 we get *y*_{2}. Hence, *y* = *G*′*y*_{1} + *H*′*y*_{2}. Let *G*′*b*_{0} = *E* and *H*′*b*_{0} = *F*. Then

## Solution around *x* = 1[edit]

Let us now study the singular point *x* = 1. To see if it is regular,

Hence, both limits exist and *x* = 1 is a regular singular point. Now, instead of assuming a solution on the form

we will try to express the solutions of this case in terms of the solutions for the point *x* = 0. We proceed as follows: we had the hypergeometric equation

Let *z* = 1 - *x*. Then

Hence, the equation takes the form

Since *z* = 1 - *x*, the solution of the hypergeometric equation at *x* = 1 is the same as the solution for this equation at *z* = 0. But the solution at z = 0 is identical to the solution we obtained for the point *x* = 0, if we replace each γ by α + β - γ + 1. Hence, to get the solutions, we just make this substitution in the previous results. Note also that for *x* = 0, *c*_{1} = 0 and *c*_{2} = 1 - γ. Hence, in our case, *c*_{1} = 0 while *c*_{2} = γ - α - β. Let us now write the solutions. It should be noted in the following we replaced each *z* by 1 - *x*.

## Analysis of the solution in terms of the difference γ − α − β of the two roots[edit]

### γ − α − β not an integer[edit]

### γ − α − β = 0[edit]

### γ − α − β is an integer and γ − α − β ≠ 0[edit]

#### γ − α − β > 0[edit]

#### γ − α − β < 0[edit]

## Solution around infinity[edit]

Finally, we study the singularity as *x* → ∞. Since we can't study this directly, we let *x* = *s*^{−1}. Then the solution of the equation as *x* → ∞ is identical to the solution of the modified equation when *s* = 0. We had

Hence, the equation takes the new form

which reduces to

Let

As we said, we shall only study the solution when *s* = 0. As we can see, this is a singular point since *P*_{2}(0) = 0. To see if it's regular,

Hence, both limits exist and *s* = 0 is a regular singular point. Therefore, we assume the solution takes the form

with *a*_{0} ≠ 0.

Hence,

- and

Substituting in the modified hypergeometric equation we get

i.e.,

In order to simplify this equation, we need all powers to be the same, equal to *r* + *c*, the smallest power. Hence, we switch the indices as follows

Thus, isolating the first term of the sums starting from 0 we get

Now, from the linear independence of all powers of *s* (i.e., of the functions 1, *s*, *s*^{2}, ..., the coefficients of *s*^{k} vanish for all *k*. Hence, from the first term we have

which is the indicial equation. Since *a*_{0} ≠ 0, we have

Hence, *c*_{1} = α and *c*_{2} = β.

Also, from the rest of the terms we have

Hence,

But

Hence, we get the recurrence relation

Let's now simplify this relation by giving *a*_{r} in terms of *a*_{0} instead of *a*_{r − 1}. From the recurrence relation,

As we can see,

Hence, our assumed solution takes the form

We are now ready to study the solutions corresponding to the different cases for *c*_{1} − *c*_{2} = α − β.

## Analysis of the solution in terms of the difference α - β of the two roots[edit]

### α − β not an integer[edit]

Then *y*_{1} = *y*|_{c = α} and *y*_{2} = *y*|_{c = β}. Since

- ,

we have

Hence, *y* = *A*′*y*_{1} + *B*′*y*_{2}. Let *A*′*a*_{0} = *A* and *B*′*a*_{0} = *B*. Then, noting that *s* = *x*^{-1},

### α − β = 0[edit]

Then *y*_{1} = *y*|_{c = α}. Since α = β, we have

Hence,

To calculate this derivative, let

Then using the method in the case γ = 1 above, we get

Now,

Hence

Hence,

For *c* = α we get

Hence, *y* = *C*′*y*_{1} + *D*′*y*_{2}. Let *C*′*a*_{0} = *C* and *D*′*a*_{0} = *D*. Noting that *s* = *x*^{-1},

### α − β an integer and α − β ≠ 0[edit]

#### α − β > 0[edit]

From the recurrence relation

we see that when *c* = β (the smaller root), *a*_{α - β} → ∞. Hence, we must make the substitution *a*_{0} = *b*_{0}(*c* − *c*_{i}), where *c*_{i} is the root for which our solution is infinite. Hence, we take *a*_{0} = *b*_{0}(*c* − β) and our assumed solution takes the new form

Then *y*_{1} = *y*_{b}|_{c = β}. As we can see, all terms before

vanish because of the *c* − β in the numerator.

But starting from this term, the *c* − β in the numerator vanishes. To see this, note that

Hence, our solution takes the form

Now,

To calculate this derivative, let

Then using the method in the case γ = 1 above we get

Now,

Hence,

Hence,

At *c* = α we get *y*_{2}. Hence, *y* = *E*′*y*_{1} + *F*′*y*_{2}. Let *E*′*b*_{0} = *E* and *F*′*b*_{0} = *F*. Noting that *s* = *x*^{-1} we get

#### α − β < 0[edit]

From the symmetry of the situation here, we see that

## Reference[edit]

- Ian Sneddon (1966).
*Special functions of mathematical physics and chemistry*. OLIVER B. ISBN 978-0050013342.